2000
DOI: 10.1111/1467-9280.00213
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Theory-of-Mind Reasoning: An Event-Related Potential Study

Abstract: Everyday understanding of human behavior rests on having a theory of mind--the ability to relate people's actions to underlying mental states such as beliefs and desires. It has been suggested that an impaired theory of mind may lie at the heart of psychological disorders that are characterized by deficits in social understanding, such as autism. In this study, we employed the event-related potential methodology to index the activity of neural systems that are engaged during theory-of-mind reasoning in adults.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
112
2
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(140 citation statements)
references
References 21 publications
18
112
2
3
Order By: Relevance
“…In recent years, finding the brain site of theory of mind has become a fashionable research enterprise (Baron-Cohen, 1995;Goel, Grafman, Sadato, & Hallet, 1995;Sabbagh & Taylor, 2000;Stone, Baron Cohen, & Knight, 1998; for a review see Frith & Frith, 1999). However, some cautionary notes can be taken from the last 20 years of cognitive neuroscience (for other criticisms on the modularity of theory of mind, see Moore, 1996).…”
Section: Future Researchmentioning
confidence: 99%
“…In recent years, finding the brain site of theory of mind has become a fashionable research enterprise (Baron-Cohen, 1995;Goel, Grafman, Sadato, & Hallet, 1995;Sabbagh & Taylor, 2000;Stone, Baron Cohen, & Knight, 1998; for a review see Frith & Frith, 1999). However, some cautionary notes can be taken from the last 20 years of cognitive neuroscience (for other criticisms on the modularity of theory of mind, see Moore, 1996).…”
Section: Future Researchmentioning
confidence: 99%
“…This addresses the emotional cost of engaging in empathy, but there is also a cognitive cost to empathy. Perspective taking and empathic accuracy are effortful processes (Epley et al, 2004;Sabbagh & Taylor, 2000;Ma-Kellems & Lerner, 2016). Based on a rich body of research finding that people are "cognitive misers"-meaning they prefer to avoid effort-researchers have found that, when given a choice, participants avoid empathy for both positive and negative experiences (Cameron et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Based on imaging and lesion experiments (12)(13)(14)(15) that study activations associated with understanding another person's mental states (16,17), we hypothesize that cooperative behavior requires the binding of contingent information that allows subjects to evaluate the mental states of their counterpart and commit to a stimuli-conditioned reward-motivated choice. This commitment allows subjects to delay their desire for immediate gratification (18) and achieve a higher cooperative reward.…”
mentioning
confidence: 99%